The second complete mitogenome of Nemipterus virgatus to dissect control region structure and phylogenetic problem of the superfamily Sparoidea (Teleostei, Perciformes). Issue 2 (3rd July 2019) - Wu, Ren-Xie; Zhai, Yun; Miao, Ben-Ben; Niu, Su-Fang; Zhang, Hao-Ran; Liu, Fang; Ou, Chun-Xiao
Abstract: In this study, we determined the complete mitogenome of Nemipterus virgatus of which the length was 17, 073 bp, including 37 canonical mitochondrial genes and 2 non-coding regions. The control region contained termination associated sequence domain (TAS), central conserved domain (CSB-F, CSB-E, CSB-D, CSB-C, and CSB-A), conserved sequence block domain (CSB-1, CSB-2, and CSB-3), and tandem repeat sequence domain (TTD). Nine single nucleotide polymorphisms and three insertion of tandem repeat sequence (each length in 28 bp) were detected between two N. virgatus mitogenomes. The phylogenetic analysis showed that the families Nemipteridae, Sparidae, Centracanthidae, and Lethrinidae did not gather into a monophyly of superfamily Sparoidea in the neighbor-joining tree.